DIMENSI KEPERDATAAN DALAM PERLINDUNGAN HUKUM ATAS ANAK JALANAN DI YOGYAKARTA - Asram AT Jadda (Madani Legal Review, 2017)
The research on “Privat Dimension Of Legal Protection For The Street Children In Yogyakarta” is the empiris legal research, aiming to investigate about privat dimension of legal protection for street children in Yogyakarta. Primary and secondary data were obtained from field research and library research. The instrumen collecting data used interview, observation, and document study. The data were then analyzed qualitatively. The research results indicate that the street children in Yogyakarta which have fluctuation mobile still haven’t gotten protection measure yet, ecspecially their identity, health, education, shelter, and jobs. Culture factors of Yogyakarta’s communities who still regard children as parent’s “asset”, the quality of education level which still low, and implementation of legislation about children protection which is irrational, irresponsible and usless influence the implementation of the street children. Protection for the street children in Yogyakarta can be done well if the parties who have a role about children protection can cooperate and coordinate well. The parties are : Children Protection Institution (LPA) DIY, Indonesian Family Planning Program Association (PKBI) DIY, Anak Mandiri Boarding House, and Legal Aid Institution (LBH) Yogyakarta. The efforts doing are assistance, founding, until reunification the children to their families needs good support from families, comunities, government, and the children too; so their rights which are protected by Convention On The Rights Of The Child on 1989 (already ratificated by KEPPRES No. 36 on 1990) can be protected.